LEGAL STATUS OF FOREIGN-FLAG VESSELS WHEN THEIR FISH-TRANSPORTATION VESSEL LICENSES HAVE BEEN REVOKED BY THE MINISTRY OF MARINE AFFAIRS AND FISHERIES - Napitupulu, Velentina (Indonesian Journal of International Law, 2017)
In combating Illegal, unregulated and unreported fishing, the Minister of Maritime Affairs and Fisheries has several times issued the ministerial decisions to revoke SIKPI (Surat Izin Kapal Pengangkut Ikan)/fish-transportation vessel license. In practice, some Indonesian fishery companies charter foreign-flag vessels to be used as fish-transportation vessel. In such cases, how is the legal status of the foreign-flag vessels when their SIKPI licenses have been revoked by the Ministry of Marine Affairs and Fisheries? In many cases, after revoking the SIKPI, the Minister of Marine Affairs and Fisheries “arrests” the vessels. Could the Indonesian Government "arrest" the vessels? What are the legal risks that could possibly arise?